Ulumul Qur’an Sebagai Kerangka Konseptual Dalam Memahami Al-Qur’an - Ahmad Husein; Azhar Nasution (Program Studi Ilmu Al-Qur'an dan Tafsir STAIN Mandailing Natal, 2026)
Equality between men and women is one of the important issues in contemporary Islamic studies. In social reality, women continue to experience discrimination and injustice in various aspects of life, such as education, employment, participation in public spaces, and decision-making processes. This condition is also influenced by religious understandings that tend to place men in dominant positions and women as subordinate parties. This study aims to analyze Amina Wadud’s thoughts on the interpretation of women from the perspective of the Qur’an and to examine the foundations of her ideas regarding gender equality in Islam. This research employs a qualitative method using a library research approach through an analysis of Amina Wadud’s works and relevant literature on gender interpretation. The findings indicate that Amina Wadud views the Qur’an as the highest source of values that justly positions men and women as equals. According to her, Qur’anic verses must be understood through a contextual approach by considering the socio-historical and cultural circumstances in which the verses were revealed. Wadud argues that the Qur’an does not legitimize male domination over women; rather, it provides equal opportunities for both men and women to develop their potential and fulfill their roles as human beings. All Qur’anic verses concerning piety (taqwa) demonstrate that human dignity is not determined by gender, but by the quality of faith and righteous deeds. Therefore, Amina Wadud’s interpretation emphasizes that Islam upholds the principles of justice and gender equality based on the values of the Qur’an.